Leadership through change: a public sector perspective - Roddis, Peter J (2010)
The research study reported in this management project examines the issues of leadership through change in the UK local authority public sector. Using the work of Senge as a guide and as an action research project, my objective was to facilitate successful positive change in the service in which I practice as a leader and manager. Consideration was given to how I could improve my work as a leader to become what Senge describes as a leader who steps ahead, who has the ‘courage, capability, and credibility to inspire change at many levels’ (Senge & Kaufer 2000:1). The project tracks and examines that process over a three year period. A major conclusion of the project is that Senge’s work appears to have provided a useful perspective to enable examination of past events and current reality. The project also appears to support Senge’s view that leaders have a significant role in sustaining change by helping to create energy through vision and passion and in managing the forces that limit change.